Spatial and socio-economic characteristics of official labour migration from neighbouring countries to Hungary - Akos Jakobi (European Regional Science Association (ERSA), 2010)
As a governmental institution the Public Employment Service in Hungary has the function to control and register official labour immigration by accomplishing regulations connected to employment permissions. As a result of the activity this institution collected a real large, and up to now basically not much explored database on the official employment of these foreign people, making it possible to find out what spatial and socio-economic features are characterising these processes. In the last decade 60-80 thousand foreign citizens were employed yearly in Hungary, of them the majority is coming from the neighbouring countries. This paper is focusing on employees coming from Romania, Slovakia and Ukraine, which countries are sending the most people to Hungary. Annually nearly 30-40 thousand low educated men of Romanian citizenship receive manual legal employment in the Hungarian labour market. The vast majority of them works in Budapest and its agglomeration as unskilled or semi-skilled workers in the construction industry, in manufacturing of machinery, in retail trade or in agriculture in the Great Plain. They are almost all Hungarians from Transylvania, for whom the Hungarian labour market grants higher safety of existence and employment with more comforts than at home. The primary motivation for their employment is the labour shortage in the Hungarian labour market. In other countries like in Slovakia different motivation factors appeared, since more skilled workers received employment in not only basic industrial and service branches. As a comparison labour migrants from Ukraine have more or less similar employment characteristics to people of Romanian citizenship.
Keywords: 330; labour migration; cross-border migration; location of activity; Hungary; Romania